AN ANALYSIS OF MATERIALS AND STUDENTS' NEEDS IN LEARNING ENGLISH : A case study at an Institute of Higher Education of Economics in Bandung - Hadijah, Diah (2010)
By using a descriptive method, this case study aims to reveal the students' needs in learning English, to identify whether the learning materials provided by lecturers accommodate the students' needs, to explore the syllabus development, and to know the students' opinions on the syllabus. This study used a qualitative approach, which is a case study, by involving seven students as respondents from an Economics Higher Education Institution in Bandung. They are from the Department of Finance and Banking, and the Department of Accounting. The data concerning students' needs in English have been collected through interview and questionnaire. Interviews and questionnaires were conducted to reveal student's needs in learning English which cover four skills of English. Meanwhile, syllabus and materials were analyzed by using framework of Dudley Evans and St. Jhon (1998) and Hutchinson and Waters (1987). The study shows that generally the learners' needs do not match to the materials provided by the lecturers that there are many reading texts taught to the students do not coincide with their field of study and the materials were categorized as General English. Further, the findings indicated that the syllabus was developed without considering principle, method of teaching and assessment. In order that syllabus is applicable the students suggested that syllabus be improved every year, the improvement should be more systematic where more lecturers are involved and objectives are aimed at designing more current relevant materials.